PENERAPAN MANAJEMEN TATA TERTIB DALAM MENINGKATKAN KEDISIPLINAN BELAJAR PESERTA DIDIK - Edi Krisnadi (Universitas Majalengka, 2020)
The research was motivated by the low discipline of students, presumably because the discipline management was not optimal. The research chosen used a qualitative approach, data collection tools with in-depth interviews, and information purposively. Data were analyzed descriptively and interpreted through data reduction, data presentation, and withdrawal. The results showed: a) disciplinary management of students was implemented through the functions of planning, organizing, implementing, and supervising; b) The strategy of implementing management through daily pickets, complementing learning facilities, extracurricular coaching; channeling interest, application of learning disciplines; c) Supporting factors in the form of a conducive and religious environment, togetherness of the family and school committee, a harmonious relationship; There are obstacles in the form of student awareness, reduction of the meaning of discipline, and the rapid flow of information through social media; d) To overcome obstacles, the principal asks for periodic reports, continuous socialization, synergizes with all parties, and collaborates with the committee; e) Discipline of learning of students increases in that, learning discipline, doing homework, and discipline outside of school. Implementation, the application of disciplinary management has a positive impact on improving student learning discipline at SMA Negeri 1 Jatitujuh